(untitled) (Open Herald: Periodical of Methodical Research, 2025)
Tetralogy of Fallot is a pathology associated with a Cyanotic congenital heart defect. Tetralogy of Fallot is characterized by hemodynamic disorders, reduced pulmonary blood flow and venous return from the right ventricle to the aorta. The main symptoms of the pathological condition are pallor of the skin, signs of cyanosis, heart murmurs, delayed regurgitation, respiratory and heart failure. This article discusses the etiology, epidemiology, clinic of Tetralogy of Fallot, as well as modern principles of pharmacological and cardiosurgical treatment of the disease.